Microwave-assisted synthesis of hematite/activated graphene composites with superior performance for photocatalytic reduction of Cr(vi). Issue 99 (24th September 2015) - Du, Yuanxin; Tao, Zhuchen; Guan, Jian; Sun, Zijun; Zeng, Wencong; Wen, Pengchao; Ni, Kun; Ye, Jianglin; Yang, Shangfeng; Du, Pingwu; Zhu, Yanwu
Abstract : α-Fe2 O3 /aMEGO composites are demonstrated to be excellent photocatalysts in Cr(vi ) reduction. Abstract : Hematite (α-Fe2 O3 ) nanoparticles are deposited onto porous 'activated microwave expanded graphite oxide' (aMEGO) carbon via a simple, rapid one-pot microwave process. Under the irradiation of visible light, the α-Fe2 O3 /aMEGO composites exhibit significantly enhanced photocatalytic activity for the reduction of Cr(vi ) to Cr(iii ). A maximum Cr(vi ) removal rate of 95.28% is obtained for the composite containing 7.72 wt% aMEGO as compared to that of 25.26% for pure α-Fe2 O3 ; the rate constant of the composite is nearly 9 times higher than that of pure α-Fe2 O3 . The crucial role of aMEGO in enhancing the photocatalytic efficiency of the composites relies not only on its large surface area, but also on the high conductivity which benefits the transport of photoexcited electrons. The enhancement in the charge separation and the suppression in the electron–hole pair recombination is evidenced by an increased photocurrent and a suppressed photoluminescence in the α-Fe2 O3 /aMEGO composites.